Derajat Anemia pada Kehamilan dengan Kejadian Asfiksia Bayi Baru Lahir - Astuti, Eka Rati; Yunita, Herlen (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
The exchange of oxygen in the blood is influenced by red blood cells. If there is interference in pregnant women can cause anemia. Anemia in pregnancy results in fetal hypoxia. Hypoxia in the fetus can cause asphyxia in the newborn. The purpose of this study was to analyze the relationship between the degree of anemia and the incidence of asphyxia in newborns at the Sumatra Island Regional General Hospital. The research design used was case-control with analytical survey techniques. Sampling was done by random sampling technique on 80 respondents. The study was conducted for one month. Data were analyzed using the chi-square test. The results showed that asphyxiated babies were born to mothers with moderate levels of anemia, while mothers with mild anemia gave birth to non-asphyxiated babies. The results of the chi-square obtained = 0,000 < 0,005, meaning that the hypothesis is accepted. It was concluded that there was a significant relationship between the degree of anemia and the incidence of asphyxia in newborns at the Sumatra Island Regional General Hospital.